PERAN PSIKOEDUKASI DALAM MEMBANGUN KESADARAN DIRI ANAK SEKOLAH DASAR TERHADAP DAMPAK PROKRASTINASI - Khairunnisa, Aliffia; Iva Prestiana, Novita Dian; Nadhirah Qintharah, Yuha (Universitas Islam 45 Bekasi, 2024)
Academic procrastination is a common issue among elementary school students, particularly those in higher grades, and is associated with low learning motivation and poor time management skills. If left unaddressed, this habit can negatively impact students’ academic performance. Therefore, this community service program aims to raise students’ awareness of the consequences of procrastination and equip them with effective time management strategies through a psychoeducational approach. The program includes socialization on academic procrastination, time management training, and motivation enhancement sessions. This initiative was implemented at SDN 01 Karang Indah, with students as the primary participants. The methods employed included interactive discussions, time management simulations, and the provision of effective learning strategies. The program’s effectiveness was evaluated by comparing students’ levels of procrastination before and after the intervention, using questionnaires and observational assessments. The results indicated a significant decrease in students’ academic procrastination levels. Participants became more aware of the negative impact of procrastination on their academic achievement and demonstrated improvements in time management skills and learning motivation. In conclusion, this psychoeducational program successfully increased students’ awareness of the importance of time management and the detrimental effects of procrastination while equipping them with practical strategies to overcome this habit. Similar programs are recommended for broader implementation to help students develop more disciplined and productive learning habits.